Physics and Chemistry of the Hydrogen Fluoride Production Process from Fluorine Containing Waste; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Dyachenko A. N. Alexander Nikolaevich; Kraydenko R. I. Roman Ivanovich; Lesnikova M. S.; Malyutin L. N. Lev Nikolaevich; Petlin I. V. Ilya Vladimirovich (2016, 2016)
Title screen